Did the world overlook the media's early warning of COVID-19?. Issue 7 (2nd August 2020) - Fu, King-wa; Zhu, Yuner
Abstract: This perspective is written to give a rapid response to discuss the role of media in risk communication in the first three months of the COVID-19 pandemic. We analyze two sets of media data, China's social media and global news event, and draw a few initial observations in relation to the impacts of China's information control policy, global risk governance, and the role of WHO.